PENGARUH DANA PERIMBANGAN (DBH, DAU, & DAK) TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) SULAWESI SELATAN - Suranto (Transpublika Publisher, 2023)
This study aims to analyze the effect of Revenue Sharing Funds (DBH), General Allocation Funds (DAU), Special Allocation Funds (DAK) on South Sulawesi's GRDP. This study uses a quantitative research design, namely research that seeks the relationship or influence between one variable and one or more other variables in terms of analyzing the effect of balancing funds on GRDP in South Sulawesi. The sample in this study looked at the budget realization reports of the Provincial Government and Regional Government of South Sulawesi Districts/Cities as well as South Sulawesi's GRDP data for 2010 to 2020. The results showed that DBH partially did not have a significant effect on South Sulawesi's GRDP. Partially, DAU has no significant effect on South Sulawesi's GRDP. Partially, DAK has no significant effect on South Sulawesi's GRDP. Meanwhile, DAU, DBH, and DAK simultaneously have a significant effect on South Sulawesi's GRDP. Furthermore, the amount of simultaneous influence is 92,6%, while the remaining 7,4% is determined by other factors not beyond this study.